Morphological variation and sexual dimorphism in the California skate, Raja inornata Jordan and Gilbert, 1881 from the Gulf of California, Mexico - Geniz, José Leonardo Castillo; Nishizaki, Oscar Sosa; Jiménez, Juan Carlos Perez (Zootaxa, 2007)
Knowledge of taxonomy, systematics and life histories of the skates that inhabit the Gulf of California is scarce. Five species have been documented in the Sea of Cortez: R. cortezensis, R. equatorialis, Raja inornata, R. rhina and R. velezi. The California skate (R. inornata) is the most abundant species caught as by-catch during the hake trawl fishery in the Gulf. Intraspecific variation in the external morphology of R. inornata from the northern Gulf of California, México is described on the basis of 24 proportional morphometric variables from 45 males (227–525 mm total length TL) and 52 females (226-690 mm TL). Males and females had 9 and 14 proportional dimensions respectively that were isometric with total length (TL). Regression slope and elevation analysis revealed that 9 relationships between TL and morphometric variables were sexually dimorphic. A stepwise discriminant function separated three groups of skates (females and males of R. inornata and males of Raja cortezensis) and was able to correctly classify 97%, 100% and 100% of the original grouped cases, respectively. The variables that best discriminated between species and sexes were preorbital length, preoral length, distance between fifth gill openings, maximum distance between pelvic fins, and distance from cloaca to anterior caudal fin. The study also revealed that several of the meristic characters examined showed considerable variation and, therefore, should be used with caution in taxonomic studies.